Fast photoinduced electron transfer through DNA intercalation. - Murphy, C J (1994)
We report evidence for fast photoinduced electron transfer mediated by the DNA helix that requires metal complexes that are avid intercalators of DNA. Here the donor bis(phenanthroline)(dipyridophenazine)ruthenium(II) [Ru(phen)2dppz2+] and acceptor bis(9,10-phenanthrenequinone diimine)(phenanthroline)rhodium(III) [Rh(phi)2phen3+] intercalate into DNA with Kb > 10(6) M-1. Luminescence quenching experiments in the presence of two different lengths of DNA yield upward-curving Stern-Volmer plots and the loss of luminescence intensity far exceeds the change in emission lifetimes. In the presence of a nonintercalative electron acceptor, Ru(NH3)3+(6), Ru(phen)2dppz2+ luminescence is quenched much less efficiently compared to that found for the intercalative Rh(phi)2phen3+ quencher and follows linear Stern-Volmer kinetics; steady-state and time-resolved Stern-Volmer plots are comparable in scale. These experiments are consistent with a model involving fast long-range electron transfer between intercalators through the DNA helix.